Factors affecting response to everolimus therapy for subependymal giant cell astrocytomas associated with tuberous sclerosis. Issue 4 (3rd January 2015) - Trelinska, Joanna; Dachowska, Iwona; Kotulska, Katarzyna; Baranska, Dobromila; Fendler, Wojciech; Jozwiak, Sergiusz; Mlynarski, Wojciech
Abstract Background The aim of the study was to investigate factors affecting response to everolimus, a mammalian‐target‐of‐rapamycin (mTOR) inhibitor, of subependymal giant cell astrocytomas (SEGA) in patients with tuberous sclerosis complex (TSC). Methods The study group consisted of 15 children with a diagnosis of TSC‐related SEGA. Median therapy duration was 13 months. Age, sex, previous neurosurgical or mTOR inhibitor treatment, everolimus blood concentration and anticonvulsant therapy were analyzed as potential factors affecting reduction of SEGA tumor volume. Results Significant reductions in SEGA volumes were noted at 3 and 6 months (median tumor volume 0.97 cm3 and 0.70 cm3, respectively, versus 2.70 cm3 at baseline, P = 0.001). Responses were observed in 11/15 (73.3%) and 10/12 (83.3%) patients at 3 and 6 months, respectively. The most rapid reduction of SEGA volume (58.6%) was found during the initial 3 months of treatment. There was no statistical difference in the extent of SEGA volume reduction between patients with everolimus trough levels <5 ng/ml and ≥5 ng/ml. Patients treated with ≤1 anticonvulsant had greater tumor reduction after 6 months of treatment. Conclusions Everolimus is an effective and safe treatment option for TSC‐related SEGA. Drug dose titration according to blood concentration did not appear to be crucial to achieve clinical efficacy; however, concomitant anticonvulsant therapy may affect response to mTOR inhibitors. Pediatr Blood Cancer 2015;62:616–621. © 2015 Wiley Periodicals, Inc.